Business plan lekor crisp & co. / Amalina Salim...[et al.] - Salim, Amalina; Amrin, Muhammad Alif; Mohd Sazali, Alia Najwa; Shaharudin, Ahmad Fauzan; Mohammad Nazri, Muhammad Nazreen Shah (2019)
LEKOR CRISP & Co. is a new setup company which supplies a food, Keropok lekor. Keropok Lekor are very well known in our country, Malaysia especially east side. This company supplies a ready-made keropok Lekor, frozen keropok lekor, sauces with various type of flavor, and also accepts for any order from the catering or wedding event. Initiate on 1st October 2017, LEKOR CRISP & Co. setup in No 1-07-01, Block 2 Presint Alami,Pusat Perdagangan Worldwide, Persiaran Akuatik Sek 13,40150 Shah Alam, Selangor Darul Ehsan. We are growth well with pre identified market size before start-up the business. Our product also give the best among the best based on the quality of the ingredient being used and the quality of the employee ethics to make sure the quality of the product is high compared to others product. Next, we are always practice a Halal way to produces the product for the customers. Lastly, we are aim to be one of the big and well known company and become an international trader. We are promising the best price with quality assurance.